A simplified method for forearm subcutaneous veins depth estimation - Goh, C.M. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents a method to measure the forearm's subcutaneous veins depth by using the theory of light propagation model. In this study, we proposed a practical method to measure the forearm's vein deep by designed an optical phantom and experiment setup to measure the diffuse reflectance (Rd). The Monte Carlo Multilayer (MCML) tool had been used to simulate the light migration into skin layer. This study is designed for those who wish to find the depth information of forearm subcutaneous vein and, in particular, for those investigating for a perfect peripheral intravenous (IVs) in clinical application. Besides covering those aspects of the measurement theory of this model, this study also includes the execution definition of the experiment setup and the fundamental design of tissue-like phantom. In this way, instructional, revision and remedial materials provide the conscientious researcher with a comprehensive text to plan and regulate for the research in vein's depth measurement. © 2016 IEEE.